Wild artefacts at two Australian museums - Innes, Tahnee (The Australian journal of anthropology, 2025)
Indigenous communities and Australian state museums appear to have settled into a truce that might best be described by Hennessy et al.'s (2013) notion of a ‘philosophy of repatriation’. This means that, after failed repatriation arguments, distance remains at the heart of the dynamic between descendant communities and their museum-stored artefacts. In the following paper, I present two stories of North Queensland Indigenous people who visited their rainforest artefacts in state museums. I conceptualise ancestralised objects as wild artefacts, where wild is invoked in two related senses. Primarily, artefacts are like wild Country: unvisited and unstable. Moreover, they are wild as in the Aboriginal English sense of wild: angry at an injustice and potentially dangerous. Artefacts might simply remain wild. Yet if North Queensland artefacts can be kept closer to Country, in regional museums for instance, this would assist the descendant community to achieve ameliorating contact and care.